A quantitative mass spectrometry method to differentiate bovine and ovine heparins from pharmaceutical porcine heparin. (1st February 2023) - Zhang, Bin; Shi, Deling; Li, Mengmeng; Shi, Feng; Chi, Lianli
Abstract: Heparin is a polysaccharide extracted from animal tissues and is used widely as an anticoagulant. In most countries, porcine intestine mucosa is the only legal source for producing heparin. It is challenging to differentiate heparins derived from porcine, ovine and bovine, especially when low amounts of ruminant heparin are adulterated into porcine heparin. Herein, we find that two marker saccharides, ΔUA2S-GlcNS6S-HexA2S (ΔISH) and ΔUA2S-GlcNAc6S (ΔIA), show significant differences in the basic building blocks of porcine heparin obtained from ruminant heparin. A quantitative mass spectrometry (MS) method was then established to selectively monitor these two marker saccharides. By using the ΔISH to ΔIA ratio, porcine heparin adulterated with a low amount of ruminant heparin (10 % ovine heparin or 5 % bovine heparin) can be differentiated. This represents a robust and sensitive method for ensuring the authenticity and safety of heparin drugs. Graphical abstract: Unlabelled Image